1969
DOI: 10.3758/bf03336546
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive conditioning with recovery from thiamine deficiency as the unconditioned stimulus

Abstract: Appetitive conditioning with recovery from thiamine deficiency as the unconditioned stimulus 50% of consumption at the beginning of the experiment, indicating that the Ss were thiamine-deficient. On Day 21, each S was given a new flavor. As soon as S had consumed a few swallows of the new flavor, it was given an intramuscular injection of thiamine hydrochloride {200 µg/kg) and then allowed to complete its 30-min drinking period. The flavor paired with the injection for the various groups was: Group .1. vanilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…This association can be learned even if the illness occurs some hours after presentation of the flavor (e.g., Garcia & Koelling, 1966;Revusky & Garcia, 1970). It has also been shown that tastes correlated with recovery from illness come to be preferred (e.g., Parker, Failor, & Weidman, 1973;Zahorik & Maier, 1969).…”
mentioning
confidence: 99%
“…This association can be learned even if the illness occurs some hours after presentation of the flavor (e.g., Garcia & Koelling, 1966;Revusky & Garcia, 1970). It has also been shown that tastes correlated with recovery from illness come to be preferred (e.g., Parker, Failor, & Weidman, 1973;Zahorik & Maier, 1969).…”
mentioning
confidence: 99%
“…Le Magnen et al concluded that a medicine effect was conditioning the learned preference. Zahorik and Maier (1969) offered rats a flavor previously paired with recovery from thiamine deficiency and found a preference for that flavor over other flavors presented in various control conditions. Rozin (1967) showed that rats with experience of sickness tend to prefer familiar flavors over novel ones.…”
mentioning
confidence: 99%
“…More frequently, the procedures by which learned aversions are produced have been compared to classical conditioning (Garcia & Ervin, 1968;P. Rozin & J. Kalat, unpublished manuscript, 1971;Zahorik & Maier, 1969): A flavor (CS) is paired with some unconditioned stimulus (poison, X-irradiation, or vitamin-deficient diet) which produces illness (UR). After one or more such pairings, the presentation of the CS alone is shown to elicit some fraction of the unconditioned response, which is called the conditioned response (CR).…”
Section: University Oj Illinoismentioning
confidence: 99%
“…Thiamine-deficient diet is an ideal US for such an experiment, because the symptoms of thiamine deficiency are well documented and many of those symptoms are easily measured in an intact, unanesthetized rat. In the present study, thiamine deficiency and temporary recovery from deficiency were paired with distinctively flavored drinking solutions in a procedure which has been shown to produce aversions to the taste paired with deficiency and preferences for the taste paired with recovery (Garcia, Ervin, Yorke, & Koelling, 1967;Zahorik & Maier, 1969). In addition to measurements of solution intake (which provide evidence for the development of aversions or preferences for tastes), several other variables known to be affected by thiamine deficiency were measured throughout the experiment.…”
Section: University Oj Illinoismentioning
confidence: 99%